Gender, Ideology and Latin American Children's Animated Television - Gonzalez-Rodriguez, Milton Fernando (Children, Youth, and International Television, 2022)
Animation allows for the creation of mediatic spaces that strengthen prevailing ideologies of masculinity and femininity. Manhood seems to operate as a key point of reference in the creation of televised animation across Latin America, especially by elevating certain heroic cultural narratives. Through a review of 21 television series, produced between 2008 and 2018, this chapter examines the portrayals of femininity and masculinity in some of the most widely broadcast animated series from the region. As a norm, Latin American illustrators adhere to the tradition of depicting female figures as secondary characters, as leading characters with a certain degree of autonomy, or as subaltern, considerate, and supportive figures. By contrast, male figures are portrayed as strong, daring, independent, and primary characters, often destined to lead their families and communities, and save their weaker friends that are typically female characters.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Argentine (corpus analysé); Belgique (lieu de production du savoir); Brésil (corpus analysé); Chili (corpus analysé); Colombie (corpus analysé); Mexique (corpus analysé); Pérou (corpus analysé); _Nettoyé

Resistance Televised: The TV da Gente Television Network and Brazilian Racial Politics - Gillam, Reighan Alexandra (Watching While Black, 2012)
As activists and political leaders in Brazil call for increasing rights, recognition, and redress to address the multiple forms of marginalization that Afro-Brazilians have endured, media has become an increasingly important sphere through which different constituencies mobilize to advance a project of racial equality. Among these groups enlisting available media resources was a group composed predominately of Afro-Brazilian media professionals who joined together to launch the TV da Gente (Our TV) television network, Brazil’s first television station with the mission to produce racially diverse programming directed toward a Black viewing audience.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé

Telenovelas and Transformation: Saving Brazil's Television Industry - Svartman, Rosane (Routledge, Taylor & Francis Group, 2021)
"This book investigates how telenovelas may be the key to the future of Brazilian television and how this content can survive in an interconnected media landscape. Recognised writer and scholar Rosane Svartman considers the particular characteristics of the telenovela format - number of episodes, melodrama influence, and influence of the audience on future writing - to explore how these can be preserved on multimedia platforms, and the challenges this change may present. Svartman further charts the transformations of the telenovela throughout its history and its major influences and unveils the main storytelling elements and writing processes. Chapters examine the business model of Brazilian corporate television within the current context of hypermedia and analyse how this relationship evolves as it is influenced by the new interactive tools and technologies that amplify the audience's power. Merging empirical practices and theory, this book will be of great interest to scholars and students of transmedia storytelling, television studies, and Latin American media, as well as professionals working in these areas"– Provided by publisher.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Brésil (corpus analysé); Brésil (lieu de production du savoir); _Nettoyé